Christian Spirituality - Dahlgrün, Corinna (SysLex, 2026)
Following an outline of the history of the term, this article presents a definition of Christian spirituality as the human response to God’s call. It describes the various forms of this response, whose foundation is the double commandment of love, and the many ways in which spirituality can be lived out in everyday life. Regularity, community, spiritual guidance, and discernment of spirits are identified as requirements for a sustainable spiritual practice in everyday life. Certain problems are then singled out, including the need to choose one’s own form of spirituality within the complex context of late modernity and the ambiguity of the concept of experience. Finally, spirituality is framed as a basis for ecumenical community.